1972
DOI: 10.1161/01.res.31.6.824
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vagal Afferents In the Control of Renal Sympathetic Nerve Activity in the Rabbit

Abstract: The influence of vagal afferents on renal sympathetic nerve activity was studied in nine rabbits anesthetized with sodium pentobarbital and artificially ventilated with oxygen. Arterial Pco 2 and pH were kept normal. The aortic depressor and the carotid sinus nerves were cut. The mean impulse frequency was determined from multifiber preparations of the renal nerve. Blood volume was altered either by bleeding or by infusing dextran. With vagi intact, an increase in blood volume of approximately 1OSE caused the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
1
3

Year Published

1976
1976
2003
2003

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 6 publications
6
56
1
3
Order By: Relevance
“…It is well documented that arterial baroreceptors are not required for the decrease in renal SNA elicited by acute VE (8,33). Our study confirms this finding because SAD did not alter the sympathoinhibitory response to acute VE.…”
Section: Discussionsupporting
confidence: 90%
“…It is well documented that arterial baroreceptors are not required for the decrease in renal SNA elicited by acute VE (8,33). Our study confirms this finding because SAD did not alter the sympathoinhibitory response to acute VE.…”
Section: Discussionsupporting
confidence: 90%
“…Our results also indicate that renal sympathetic tonic activity is present during extracellular volume expansion, consistent with the earlier observation that efferent renal nerve activity is reduced but not abolished after a 10% increase in blood volume (11).…”
Section: Introductionsupporting
confidence: 93%
“…During maximal postarrhythmic renal vasoconistrictioni (4 min) renal capsular catecholamines were threefold higher than femoral arterial levels. Comparison of changes in femoral arterial catecholamine levels in these six dogs in response to atrial fibrillation revealed no significanit difference from those seen in the nine animals reported in Table II. The changes from preintervention control hemodvnamics to control hemodynamiiics during an intervention (SQ 20881, phentolamine, propranolol, vagal cooling, atropine renal denervation, bretylium, and hexamethonium) were the same as have been previously reported in the pentobarbital-anesthetized dog and will not be discussed further unless appropriate to the focus of this study (10)(11)(12)(13)(14). tribution of blood flow have been observed in response his study caused a dis-to exercise in the conscious dog with complete heart ion of renal blood flow block (15).…”
Section: Resultsmentioning
confidence: 91%